Attitudes of Black Americans, Towards Police Misconduct in an Urban Area - Armstead, Demetric Rayshawn (2019)
Little is known about Black Americans' experience with and attitudes toward the police. For Black Americans and the police to improve their relationship, police need to understand the factors that influence Black Americans' perceptions. Asante's concept of Afrocentric theory assisted with exploring the attitudes of Black Americans about police misconduct in a Southeastern United States urban area. The purpose of the qualitative ethnographic study was to understand the attitudes of Black Americans towards the police and the factors that influence those perceptions. This study precisely addresses three main questions: (1) how has media coverage impacted Black Americans' perceptions of officer behavior in the urban area; (2) how has the community environment impacted Black American perceptions of officer behavior in the urban area; and (3) how have officers' informal and formal behaviors impacted Black Americans' perception of police conduct in the urban area. A purposive sampling strategy was used to recruit 30 Black Americans for the semi-structured interviews who discussed their thoughts and opinions about factors that are associated with the Black American community. The data were coded resulting in 12 themes. Results from this study indicated that the majority of Black Americans had overall negative views about the police. The findings suggest that social change can only happen when the police and Black Americans work together to understand each other and address issues that come with a lack of understanding. Promoting good relationships through media, the community environment, and improving police encounters with the Black American community is critical to enhancing community relations